Housing and psychosocial factors associated with mental health in children aged 6–12 years from homeless families in the Greater Paris area, France: the ENFAMS cross-sectional study - Estevez, Mégane; Oppenchaim, Nicolas; Descarpentrie, Alexandra; Rambliere, Lison; Douay, Caroline; Galera, Cédric; Vandentorren, Stéphanie (Frontiers in Child and Adolescent Psychiatry, 2023)
Introduction: This study aimed to identify the psychosocial factors associated with mental health disorders in children aged 6 to 12 years living in sheltered homeless families in the Île-de-France region (France), with a view to guiding the development of actions that could improve their mental health. Method: The cross-sectional study ENFAMS was conducted in sheltered homeless families using face-to-face questionnaires administered by trained interviewers and psychologists in 17 languages. The questionnaires collected data on sociodemographics, living conditions, and health characteristics for children and parents. Mental health disorders were assessed in 198 children using the Dominic Interactive. Statistical analyses were performed using multiple linear regression. Results: The Dominic Interactive mean score was 28.8 (SD=17.5), and 25.3% of the children had a possible or probable mental health disorder. Factors associated with a higher risk of a mental health disorder were parents’ irregular administrative status, living with three or more siblings, not attending school, being bullied at school, underweight, and hospitalization in the previous 12 months. Conclusion: Our findings highlight the importance of psychosocial determinants in children’s mental health, and underline the need for prevention actions for homeless families which focus on improving living, schooling, and healthcare conditions, especially greater access to mental health care.